2013
DOI: 10.1007/s10863-013-9505-0
|View full text |Cite
|
Sign up to set email alerts
|

Decline in cytochrome c oxidase activity in rat-brain mitochondria with aging. Role of peroxidized cardiolipin and beneficial effect of melatonin

Abstract: Reactive oxygen species (ROS) are considered a key factor in mitochondrial dysfunction associated with brain aging process. Mitochondrial respiration is an important source of ROS and hence a potential contributor to brain functional changes with aging. In this study, we examined the effect of aging on cytochrome c oxidase activity and other bioenergetic processes such as oxygen consumption, membrane potential and ROS production in rat brain mitochondria. We found a significant age-dependent decline in the cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 62 publications
4
25
2
Order By: Relevance
“…The loss of cardiolipin can explain the decreased mitochondrial membrane fluidity reported in aged rats (Lee et al ., ). It is also consistent with the findings that age‐related decline in complex IV activity can be restored by exogenously added cardiolipin or cyt c (Paradies et al ., ; O'Toole et al ., ; Petrosillo et al ., ).…”
Section: Aging Leads To Alterations In Lipid Composition Of the Immmentioning
confidence: 97%
“…The loss of cardiolipin can explain the decreased mitochondrial membrane fluidity reported in aged rats (Lee et al ., ). It is also consistent with the findings that age‐related decline in complex IV activity can be restored by exogenously added cardiolipin or cyt c (Paradies et al ., ; O'Toole et al ., ; Petrosillo et al ., ).…”
Section: Aging Leads To Alterations In Lipid Composition Of the Immmentioning
confidence: 97%
“…By doing so, melatonin is believed to protect against ischemia-reperfusion induced damage to the heart [138]; it also attenuates mitochondrial dysfunction in sepsis [139,140], multiple sclerosis [141], doxorubicin-induced cellular senescence [142], in senescence-accelerated mice [143][144][145], and during aging [134,[146][147][148]. It was also found that the protection of cardiolipin from peroxidation in mitochondria was an important means by which melatonin prevents mitochondrial dysfunction [138,146,[149][150][151].…”
Section: Protection and Improvement Of Mitochondrial Function By Melamentioning
confidence: 99%
“…Melatonin as a mitochondrial antioxidant protects cardilipin from pro-oxidation and therefore maintains the closed configuration of AAC. The protective effects of melatonin on cardilipin and MPTP are well documented [164,165,166,167]. …”
Section: Melatonin: a Potent Protector Of Mitochondriamentioning
confidence: 99%